2010
DOI: 10.1074/jbc.m109.073338
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Imaging of Epidermal Growth Factor Receptor Clustering

Abstract: The development of some solid tumors is associated with overexpression of the epidermal growth factor receptor (EGFR) and often correlates with poor prognosis. Near field scanning optical microscopy, a technique with subdiffraction-limited optical resolution, was used to examine the influence of two inhibitors (the chimeric 225 antibody and tyrosine phosphorylation inhibitor AG1478) on the nanoscale clustering of EGFR in HeLa cells. The EGFR is organized in small clusters, average diameter of 150 nm, on the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 51 publications
10
92
0
Order By: Relevance
“…The amount of EGFR complexes also increases upon EGF stimulation at different doses, leading to the formation of larger oligomers, which are then endocytosed at different rates and possibly with different fates. As shown earlier, the low-dose EGF stimulation (10 ng/mL) leads to the recycling of the receptors while high-dose EGF (100 ng/mL) to receptor degradation (33,74).…”
Section: Discussionmentioning
confidence: 55%
“…The amount of EGFR complexes also increases upon EGF stimulation at different doses, leading to the formation of larger oligomers, which are then endocytosed at different rates and possibly with different fates. As shown earlier, the low-dose EGF stimulation (10 ng/mL) leads to the recycling of the receptors while high-dose EGF (100 ng/mL) to receptor degradation (33,74).…”
Section: Discussionmentioning
confidence: 55%
“…Previous study using near-field scanning optical microscopy (NSOM) suggested that EGFR might be organized in aggregates with distinct diameters in the membrane of paraformaldehyde-fixed Hela cells [18]. However, the detailed information of EGFR distribution on cell surface, especially on living cell surface, still remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…6D and 7B ), the EGFR showed clustering over a broader size range (25-150 nm). Such submicron-scale clustering of the EGFR in cellular plasma membranes has been previously characterized by immuno-EM ( 11,39 ) and single molecule-resolution fl uorescence microscopy (40), although the factors responsible for the establishment of these microdomains are the subject of continuing investigation ( 7,(39)(40)(41). By analyzing the co-clustering of the EGFR and Lck-BAP-GFP reporter with the bivariate Ripley's K function statistic ( Fig.…”
Section: Discussionmentioning
confidence: 99%